Occupational noise-induced hearing loss in high-income countries: A multi-country analysis of compensation records - Nyasha Makaruse; Michael R.D. Maslin; Ziva Shai Campbell (Heliyon)
Background: Occupational Noise-Induced Hearing Loss (ONIHL) presents a significant occupational health challenge worldwide, with profound economic and societal implications. This study assesses socio-demographics of ONIHL cases, calculates incidence rates and trends (2013–2022), compares ONIHL burden with other occupational diseases, and quantifies annual compensation costs across Australia, Canada, Germany, Hong Kong and New Zealand. Materials and Methods: A retrospective analysis of ONIHL compensation data sourced from governmental compensation records in five high-income countries was conducted. Incidence rates were computed based on accepted compensation cases per employed workforce and analyzed over a decade-long study period. Results: A total of 131,433 newly compensated ONIHL cases were identified across five countries. Males accounted for 96.3 % of cases, with varying age distributions observed among countries. The construction and manufacturing sectors consistently emerged as primary contributors to ONIHL. ONIHL ranked among the top three occupational conditions in all study countries, with incidence rates ranging from 5 to 148 per 100,000 employed workers. Compensation costs for rehabilitation exceeded USD 800 million during the study period, with Germany incurring the highest expenses. Conclusion: Our findings emphasize the need for intensified ONIHL prevention efforts, particularly within the manufacturing and construction industries across high-income countries. The study highlights the disproportionate representation of older males among the new ONIHL cases, whether due to their concentration in noisy settings or inherent susceptibility to noise-induced hearing changes. The financial costs are substantial, with nearly USD 2 billion spent on ONIHL compensation over the study period, including pension costs for ONIHL cases in Germany. This study illuminates the significant burden of ONIHL as a leading occupational disease, offering insights for areas to target intensified prevention and interventions efforts for accelerated reduction in new ONIHL cases.